Distribution of fossil marine vertebrates in Cerro Colorado, the type locality of the giant raptorial sperm whale Livyatan melvillei (Miocene, Pisco Formation, Peru). Issue 3 (26th May 2016) - Bianucci, Giovanni; Di Celma, Claudio; Landini, Walter; Post, Klaas; Tinelli, Chiara; de Muizon, Christian; Gariboldi, Karen; Malinverno, Elisa; Cantalamessa, Gino; Gioncada, Anna; Collareta, Alberto; Gismondi, Rodolfo-Salas; et al.
Abstract : Hundreds of fossil marine vertebrates cropping out at Cerro Colorado (Pisco Basin, Peru) are identified and reported on a 1:6500 scale geological map and in a joined stratigraphic section. All the fossils are from the lower strata of the Pisco Formation, dated in this area to the late middle or early late Miocene. They are particularly concentrated (88%) in the stratigraphic interval from 40 to 75 m above the unconformity with the underlying Chilcatay Formation. The impressive fossil assemblage includes more than 300 specimens preserved as bone elements belonging mostly to cetaceans (81%), represented by mysticetes (cetotheriids and balaenopteroids) and odontocetes (kentriodontid-like delphinidans, pontoporiids, ziphiids, and physeteroids, including the giant raptorial sperm whale Livyatan melvillei ). Seals, crocodiles, sea turtles, seabirds, bony fish, and sharks are also reported. Isolated large teeth of Carcharocles and Cosmopolitodus are common throughout the investigated stratigraphical interval, whereas other shark teeth, mostly of carcharinids, are concentrated in one sandy interval. This work represents a first detailed census of the extraordinary paleontological heritage of the Pisco Basin and the basis for future taphonomic, paleoecological, and systematic studies, as well as a much needed conservation effort for this extremely rich paleontological site.